First report of acute African swine fever in pig farms on the west coast of India: pathological and molecular insights - Narnaware, Shirish Dadarao; Rajkumar, Susitha; Vemula, Prasastha; Udharwar, Sanjay V.; Sahu, Amiya Ranjan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAfrican swine fever (ASF) represents one of the most devastating viral threats to global pig production, with mortality often approaching 100% and severe socioeconomic consequences. India confirmed its first ASF outbreaks in 2020 in the north-eastern states, but no cases had previously been documented on the west coast. This study presents the first confirmed ASF outbreaks in pig farms on India’s west coast, providing clinicopathological and molecular insights.MaterialsBetween January and June 2025, two pig farms in North Goa experienced unusually high mortalities. The affected pigs were clinically examined, and necropsies were performed on eight carcasses for detailed pathological analysis. Tissue samples (spleen, kidneys, lungs, liver, and lymph nodes) and blood were collected for histopathology and polymerase chain reaction (PCR)-based diagnosis. African swine fever virus (ASFV) was detected using PCR targeting the B646L gene, which encodes the major capsid protein p72, for molecular confirmation. For genotyping, the partial B646L (p72) gene and the complete E183L (p54) gene were amplified, sequenced, and subjected to phylogenetic analysis.ResultsBoth farms exhibited extremely high mortality (95%–96%), with affected pigs showing fever, depression, cyanosis, respiratory distress, and widespread cutaneous hemorrhages. Gross pathology revealed splenomegaly, hepatomegaly, severely congested kidneys with petechial hemorrhages, hemorrhagic lymphadenopathy, and vascular congestion. Histopathology demonstrated severe lymphoid depletion, necrosis, and hemorrhages in the spleen and lymph nodes, along with glomerulonephritis in the kidneys. ASFV was confirmed by PCR in all samples. Phylogenetic analysis placed the isolates in genotype II, showing complete identity with earlier Indian and Asian strains, indicating continued circulation of this lineage in the region.ConclusionThe emergence of ASF in Goa highlights the spread of genotype II to India’s west coast, underscoring the urgent need to strengthen farm biosecurity, raise farmer awareness, and implement active surveillance to protect the expanding pig sector from severe economic losses.